The effect of Ga-mee-gwui-ryong-tang and Yuk-mee ji-hwang-tang Herbal-acupuncture on the growth of mice - Min-jung Kim; Kwon-eui Hong (Korean Pharmacopuncture Institute, 2006)
Objectives : To investigate the effect of Ga-mee-Gwui-ryong-tang herbal acupuncture (GR-HA) at GB39 and ST36 and the effect of Yuk-mee ji-hwang-tang herbal acupuncture (YM-HA) at GB39 and KI10 on growth in mice. Methods : Mice were divided into 7 groups(n=10) ; saline-ST36, saline-GB39, saline-KI10, GR-HA-ST36 group treated with GR-HA at right ST36, GR-HA-GB39 group treated with GR-HA at right GB39, YM-HA-GB39 group treated with YM-HA at right GB39, YM-HA-KI10 group treated with YM-HA at right KI10. Saline-ST36 group, saline-GB39 group and saline-KI10 group were injected with saline at right ST36, GB39, KI10 respectively. Saline injection and HA were performed 3 times a week for 18 days. The length(total height, body length and tail length), weight and the protein efficiency ratio were measured as well as IGF-1 level in serum. Results : 1. GR-HA at GB39 and GR-HA at ST36 promoted growth in weight, tail length and total height but there was no statistical significance. 2. GR-HA at GB39 significantly promoted protein efficiency on the 14th day and GR-HA at ST36 on the 3rd day. 3. GR-HA at GB39 significantly increased serum IGF-1. GR-HA at ST36 increased IGF-1 slightly but with no statistical significance. 4. YM-HA at GB39 and YM-HA at KI10 promoted growth in weight, height, tail length and total height but there was no statistical relevance. 5. YM-HA at GB39 and YM-HA at KI10 significantly promoted protein efficiency on the 14th day. 6. YM-HA at GB39 and YM-HA at KI10 significantly increased serum IGF-1. Serum IGF-1 level of YM-HA-KI10 group was significantly higher than that of YM-HA-GB39 group. 7. Serum IGF-1 level of GR-HA-GB39 group was significantly higher than that of YM-HA-GB39 group. Conclusions : GR-HA and YM-HA both may promote growth. This study suggests that herbal acupuncture at GB39 is more effective with Gwui-ryong-tang than Yuk-mee ji-hwang-tang to promote growth. It also suggests that Yuk-mee ji-hwang-tang herbal acupuncture is more effective at KI10 than at GB39.